Penggunaan Badan Hukum Perkumpulan terhadap Badan Usaha Milik Desa: Bagaimana Kedudukan dan Implikasinya? - Igirisa, Ridwanto; Ali, Gito Alan; Sahabat, Andi Inar; Nur, Rafika (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2022)
Village Owned Enterprises (BUM Desa) have a very strategic role in improving the economy, especially in South Suwawa District, Bone Bolango Regency, Gorontalo Province. BUM Desa is formed by the Village Government in order to maximize the entire economic potential of the village. This study discusses how the position and implications of the use of association legal entities by BUM Desa in improving the village economy in South Suwawa District, Bone Bolango Regency. The research method used in this research is juridical-empirical type, data collection techniques obtained through observation are then processed and analyzed descriptively. The purpose of this study is that BUM Desa has strong legality in improving the village economy in South Suwawa District in particular and Bone Bolango Regency in general, as well as how to overcome economic problems that arise in the future.